2020
DOI: 10.3390/su12093632
|View full text |Cite
|
Sign up to set email alerts
|

Cause-Related Marketing Influence on Consumer Loyalty in a Medium-Sized City

Abstract: The purpose of this study is to analyze the effect of the performance of a cause-related marketing action on consumer loyalty by a company. In addition, the study explores the moderating effect of the publicizing medium. The proposed theoretical model was tested based on data gathered from a face-to-face questionnaire completed by 421 respondents living in a medium-sized city. The results validated the proposed model and showed that the functional and image fit between social actions and companies are key ante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 71 publications
0
6
0
1
Order By: Relevance
“…As advocated by Connell and Meyer [99], such coordination will make film-induced tourism more intense. Of course, this approach must have the image of the destination as a fundamental point, creating or projecting an adequate image that allows the destination to take advantage of the benefits of film tourism as much as possible [88,100]. This image must certainly show a true picture; it must be authentic, evocative and attractive.…”
Section: General Implications and Limitationsmentioning
confidence: 99%
“…As advocated by Connell and Meyer [99], such coordination will make film-induced tourism more intense. Of course, this approach must have the image of the destination as a fundamental point, creating or projecting an adequate image that allows the destination to take advantage of the benefits of film tourism as much as possible [88,100]. This image must certainly show a true picture; it must be authentic, evocative and attractive.…”
Section: General Implications and Limitationsmentioning
confidence: 99%
“…The CRM-related topic has been widely researched in previous studies, which suggested different perspectives to CRM and various outcomes (Furman and Maison, 2020;Chaabouni et al, 2021;Surianto et al, 2020;Jeon and An, 2019;Vrontis et al, 2020;Santoro et al, 2020;Nair, 2020;Molinillo et al, 2020;Furman and Maison, 2020;E Silva et al, 2019;Baek et al, 2020). CRM can lead to repeat purchases by existing customers (Surianto et al, 2020); repurchase intention (Moslehpour et al, 2017); purchase and repurchase intention (Varadarajan and Menon, 1988;Kotler and Lee, 2005;Kotler and Keller, 2012); improved Perceived corporate social responsibility brand image (BIMA); and improved brand awareness; enhanced corporate reputation and positive corporate image (Surianto et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…, 2020; Santoro et al. , 2020; Nair, 2020; Molinillo et al. , 2020; Furman and Maison, 2020; E Silva et al.…”
Section: Introductionmentioning
confidence: 99%
“…The current new retail era emphasises the combination of online and offline recycling channels to accomplished collaboration between retailers and manufacturers [31][32][33][34][35]. It helps to achieve cross-channel recycling, which improves consumer loyalty and satisfaction, as well as achieve efficient operation of CLSC recycling [36][37][38][39]. Under the traditional recycling model for both online and offline sale, the intact second-hand products can be sold through retailers into the second-hand market and used products can be recycled through manufacturers for reprocessing and reuse.…”
Section: Introductionmentioning
confidence: 99%